Nowości w diagnostyce jaskry - Szewczuk, Alina; Zaleska-Żmijewska, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2023)
Glaucoma is the leading cause of irreversible blindness worldwide. It is characterized by progressive loss of retinal ganglion cells and their axons. Glaucoma usually becomes symptomatic only in its severe stages. Therefore, the major challenge to try to prevent visual loss is to identify the disease before it becomes symptomatic. Here we review recent progress in the development of new technologies for detecting and monitoring glaucoma. This review describes most promising findings in tonometry, retinal imaging, visual function testing, electrophysiology and artificial intelligence. The widespread use of new technologies will be useful for clinical diagnosis, prediction of progression and improvement in health care delivery.